Comparative Therapeutic Efficacy of 153Sm-EDTMP and 177Lu-EDTMP for Bone Pain Palliation in Patients with Skeletal Metastases: Patients’ Pain Score Analysis and Personalized Dosimetry - Sharma, Sarika; Singh, Baljinder; Koul, Ashwani; Mittal, Bhagwant Rai (Frontiers in Medicine, 2017)
Introduction: The aim of the present study was to compare the therapeutic efficacy of 153SmEDTMP and 177LuEDTMP in pain palliation in cancer patients with skeletal metastases. Materials and methods: Thirty patients (25 M: 5 F, mean age: 66.0 ± 14.7 years) of breast/prostate cancer with documented skeletal metastases were recruited prospectively. Twenty patients were considered randomly for treatment with 153Sm-EDTMP and 10 patients with 177Lu-EDTMP respectively. Using fixed dose of 37.0 MBq/Kg. body weight of each, the mean administered doses of 153Sm-EDTMP and 177Lu-EDTMP were 2155.2 ± 419.6 MBq (1347.0 -2857.0) and 1935.1 ± 559.4 MBq (1073.0-2627.0) respectively. Anterior and posterior whole body images were acquired at different time points following radioactivity administration. The first data set of pre-void images (acquired at 0.5h) representing the total activity of either of 153Sm-EDTMP or 177Lu-EDTMP was considered as reference images. All the serial images were used for patients’ dosimetry analysis by using OLINDA algorithm. Reduction in pain scoring was assessed clinically over 8 –weeks by using appropriate WHO criteria and correlated with the absorbed dose to the metastatic sites. Results: A total of 86 metastatic lesions clearly visualized on post therapy serial images (matching on bone scans) were evaluated for absorbed dose calculations. Both 153Sm-EDTMP and 177Lu-EDTMP delivered similar absorbed dose to the metastatic sites i.e. 6.22 ± 4.21 mSv/MBq and 6.92 ± 3.92 mSv/MBq respectively. The mean absorbed doses to various other organs were found to be comparable and within the safe limits. A complete response for each radionuclide was evaluated as 80.0 %. No significant alternation in blood parameters and no untoward reaction was observed. However, a mild to severe toxicity was observed in 2 patients (1 each with 153Sm-EDTMP and 177Lu-EDTMP). Kaplan-Meier survival analysis demonstrated that 27/30 patients had pain free survival (complete response) up to the observational period of 8 weeks. However, no statistically significant correlation could be established between the pain scoring and absorbed dose to metastatic sites. Conclusion: Both the radionuclides thus offer an effective and comparable therapeutic efficacy for bone pain palliation at an affordable cost and can be used interchangeably as per the availability.